Built for more : the role of out-of-school time in preparing youth for the future of work - Sanders, Byron (Education); Epner, Shannon (Current issues in out-of-school time., 2024)
"Built for More, The Role of OST in Preparing Youth for the Future of Work will highlight OST research and illustrative practices and bring forward multi-disciplinary perspectives about future trends, innovations, and the impact of OST on the future workforce. The focus is on OST programs as well as related activities that contribute to employability, such as summer work, internships, apprenticeships, disability inclusion, career-focused mentoring, and more. The book will also lift up voices traditionally left out of the OST conversation, including BIPOC, rural, and other marginalized communities. Given that the world of work is rapidly evolving, what are the most important ways we should be framing education and youth development work? Define forces and illuminate the trends reshaping the necessary skills that youth will need to thrive professionally, personally, and to positively impact their communities. What are the skills that employers are saying are most valuable due to transformation from automation, machine learning, and the 4th industrial age we are experiencing globally? What are key demographic shifts that add urgency to the imperative for change in our human development ecosystems?"--